Development and validation of a food-related quality of life questionnaire (CANUT-QVA) for cancer patients - Kenza Drareni; Catherine Mercier; Reisya Rizki Riantiningtyas; Anestis Dougkas; Benjamin Riche; Pascale Roux; Chantal Fingal; Hélène Labrosse; Fadila Farsi; David Dayde; Mélanie Roche; Julie Anne Nazare; et al. (Clinical Nutrition Open Science)
Summary: Background: Monitoring the psychosocial, emotional, and hedonic aspects of food behaviour is important for understanding cancer patients' distress and reducing the risk of malnutrition. However, there is no specific tool to measure food-related quality of life of cancer patients. This study aimed to develop and validate a questionnaire that assesses food-related quality of life in cancer patients. Methods: Relevant items from existing food-related quality of life assessment tools were selected to compose the present 46-item questionnaire. The questionnaire was validated in 276 healthy controls and 173 cancer patients. Exploratory Factor Analysis (EFA) and multiple correspondence analysis were performed for both groups to determine construct and discriminant validity. Analysis of test-retest reliability was also performed to evaluate reproducibility. Results: Out of the 46 items, 39 items showed significant differences between patients and healthy controls. The EFA allowed the identification of 9 factors in the food-related quality of life: 1. Cooking enjoyment/COOK; 2. Attention to nutrition/NUTRI; 3. Attention to meal quality and variety/QUAL; 4. Adaptive dietary practices/ADAPT; 5. Hedonic appreciation/HEDO; 6. Sensory alteration/ALT-SENS; 7. Meal experience/ALT-MEAL; 8. Altered digestion/ALT-DIGE; and 9. Dining & commensality/SOCIO. Four subscores (ADAPT, ALT-SENS, ALT-MEAL, ALT-DIGE) exhibited significant discriminant validity across controls and patients. ALT-SENS (p=0.016), ALT-MEAL (p=0.04), and ALT-DIGE (p=0.009) were higher in patients undergoing chemotherapy compared to patients not undergoing chemotherapy. The questionnaire showed good test-retest reliability. Conclusions: This questionnaire offers valuable insights for clinical research on the impact of cancer on patients' relationships with food.